OPTIMASI RUANG DAGANG PASAR JOHAR SEMARANG - Isna Pratiwi; Suzanna Ratih Sari; Agung Budi Sardjono; Sukawi Sukawi (Universitas Katolik Soegijapranata, 2025)
Along with the development of the times, traditional markets continue to exist today. Johar Market is a traditional market that is still a traditional shopping center in the city of Semarang. The revitalization process at Johar Market in 2015 made Johar Market a new market that complies with SNI standards. The revitalization was carried out as an effort by the government to restore the cultural heritage building after it burned down. The restoration of the form and design of Johar Market, which was first inaugurated in 1839, was done in order to restore the essence of the cultural heritage building. The restoration of the form of Johar Market caused changes in the spatial trading space and the behavior of traders in order to adapt to the new form. This study aims to identify the optimization of trading space within the Johar Traditional Market in Semarang. The method used in this study is a descriptive qualitative method followed by an in-depth analysis of the trading space. The study results indicate that the arrangement of merchandise in Johar Market is a social activity of traders that demonstrates togetherness and a sense of brotherhood among traditional market traders.